Enhancing drought tolerance in common bean by plant growth promoting rhizobacterium Bacillus amyloliquefaciens - Anika ANZUMA; Md. Motaher HOSSAIN; Mohammed MOHI-UD-DIN; Anika NAZRAN; Haider Iqbal KHAN; Shah Mohammad Naimul ISLAM; Totan Kumar GHOSH (Acta Agriculturae Slovenica)
The study was made to explore the implications of plant growth promoting rhizobacterium in French bean while acclimating to drought stress. Among the bacterial strains used in this study, Bacillus amyloliquefaciens (PPB6) was selected as the suitable candidate for having better growth performances in French bean. Plants provided with drought and PPB6 showed better performances in morpho-physiological attributes as compared to drought-stressed plants only. While facing drought, PPB6 reduced Reactive Oxygen Species (ROS); hydrogen peroxide (H2O2), and lipid peroxidation product; malondialdehyde (MDA), and electrolyte leakage as compared to drought-stressed plants only. Consistently, PPB6 reduced proline, total phenolics and flavonoid contents under drought stress than drought-stressed plants only. Besides, significant reduction of the activity of ascorbate peroxidase, glutathione S-transferase and peroxidase by PPB6 suggesting the lowering of drought-induced oxidative damage by this bacterium. Although, control plants showed best performance in the induction of morpho-physiological parameters and reduction of antioxidative properties, the better permeances in this regard by the plants treated with drought and PPB6 than drought-stressed only, suggesting that PPB6 has the ability to reduce the drought impacts and could partially complements the features of non-stressed control plants. We suggest PPB6 as the potential mitigator of the drought stress in French bean.